INTERNATIONAL LEGAL SUPPORT FOR AIR TRAFFIC MANAGEMENT - Polishchuk, Inna; Sirenko, Sofia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to identify and analyse the peculiarities of modern international legal support for air traffic management and to assess its implementation in the system of national regulatory and legal regulation. Research methods: the methodological basis of the study is based on general scientific methods of scientific knowledge: system-functional, formal-logical, comparative, dialectical, statistical, forecasting and others; as well as special legal methods: comparative legal, formal legal, classification method and others. Results: the article proves that air traffic management, as a dynamic, integrated management of air traffic and airspace, is currently one of the most important components among the mandatory ground support facilities required for the safe and efficient operation of air traffic, the current ICAO standards and recommended practices, rules and procedures of other international aviation organisations on air traffic management are the basis of international legal support for air traffic, which are established to ensure flight safety and, in general, the safety of civil aviation at the current stage of its functioning; minimising the risk of accidents and disasters; ensuring cooperation between airlines and air traffic services of different countries; promoting air traffic optimisation and flight efficiency, increasing the efficiency of airspace use, which in turn reduces airlines’ costs and improves passenger service. Therefore, such international standards and recommendations should be more fully taken into account by all ICAO Member States when formulating and updating their national legislation to ensure the safety, efficiency and stability of aviation activities and the use of airspace in the context of globalisation, rapid technological development, as well as taking into account current threats and risks. Discussion: international legal support of air traffic, study of problems related to improvement and modernisation of its regulation is a key factor for ensuring international security, efficiency and stability of aviation activities related to the use of airspace in the context of globalisation and rapid technological development. After all, innovations in aviation technology require updating and harmonising regulatory legal standards to integrate new systems and ensure their compatibility with existing ones. At the same time, the international legal framework for air traffic management involves complex political and legal issues related to the sovereignty of states, flight rights, the legal regime of airspace, etc. Research in this area allows us to better understand current challenges and opportunities, contribute to the development of more efficient and safer regulatory systems, and formulate policies that meet the interests of all participants in the international aviation market.